Vagrants and Vagabonds : Poverty and Mobility in the Early American Republic - O'Brassill-Kulfan, Kristin; O'Brassill-Kulfan, Kristin (Book collections on Project MUSE., 2019)
""Vagrants and Vagabonds: Poverty and Mobility in the Early American Republic" explores the topics of social class and poverty and their implications in the early American republic." ... Provided by publisher.